Student activism in Niger: subverting the 'limited pluralism', 1960–83. (16th January 2019) - Smirnova, Tatiana
Abstract: This article revisits the modern political history of Niger during the 1960s to the 1980s through an analysis of relations between student activists and government authorities. It explores how a student organization, the Union des Scolaires Nigériens (USN), managed to bypass multiple layers of political control to become a well-structured political movement, capable of seriously challenging the legitimacy of the authorities. Specifically, the article examines interactions between the USN and different bodies of political power, including the Diori and Kountché governments, in the larger context of regional solidarities and the Cold War. It analyses key moments of this struggle by showing how two generations of student leaders (those of the 1960s to early 1970s and the late 1970 to early 1980s) nourished the creation of specific windows of political action, which found various outlets for expression depending on the form of state power as well as the form and methods of activist work. Résumé: Cet article revisite l'histoire politique moderne du Niger des années 1960 aux années 1980 à travers l'analyse des relations entre étudiants activistes et autorités gouvernementales. Il explore comment une organisation d'étudiants, l'Union des scolaires nigériens (USN), est parvenue à contourner plusieurs strates du contrôle politique pour devenir un mouvement politique bien structuré capable de défier sérieusement la légitimité des autorités. En particulier, l'article examine les interactions entre l'USN et les différents organes du pouvoir politique, y compris les gouvernements Diori et Kountché, dans le contexte plus large des solidarités régionales et de la guerre froide. Il analyse les moments clés de cette lutte en montrant comment deux générations de leaders étudiants (celle de la période 1960-début des années 1970, et fin des années 1970-début des années 1980) ont favorisé la création de fenêtres d'action politique spécifiques qui ont trouvé diverses voies d'expression selon la forme de pouvoir d'État, mais aussi selon la forme et les méthodes de travail activiste.